CRISPR/Cas System and Factors Affecting Its Precision and Efficiency - Javaid, Nasir; Choi, Sangdun (Frontiers in Cell and Developmental Biology, 2021)
The diverse applications of genetically modified cells and organisms require more precise and efficient genome-editing tool such as clustered regularly interspaced short palindromic repeats/CRISPR-associated protein (CRISPR/Cas). The CRISPR/Cas system was originally discovered in bacteria as a part of adaptive-immune system with multiple types. Its engineered versions involve multiple host DNA-repair pathways in order to perform genome editing in host cells. However, it is still challenging to get maximum genome-editing efficiency with fewer or no off-targets. Here, we focused on factors affecting the genome-editing efficiency and precision of CRISPR/Cas system along with its defense-mechanism, orthologues, and applications.